Effect of acute transcranial magnetic stimulation on intracellular signalling in human skeletal muscle - von Walden, F; Gidlund, E; Liu, C; Ramstrand, N; Norrbom, J; von Wachenfelt, N; Kjellgren, H; Sundberg, C; Pontén, E; Alkner, B (Journal of rehabilitation medicine, 2020)
To investigate the potential of an acute bout of transcranial electrical stimulation to induce anabolic signalling. Experimental intervention on healthy subjects. Ten healthy subjects, 5 women and 5 men (mean age (standard deviation (SD) 32 years (SD 4)). The quadriceps muscle was stimulated at a frequency of 10 Hz for 10 s, followed by 20 s of rest, repeated 40 times over 20 min. Electromyography and force data were collected for all transcranial electrical stimulation sequences. Muscle biopsies were obtained from the vastus lateralis muscle before and 1 and 3 h after stimulation. One bout of transcranial electrical stimulation decreased phosphorylation of AKT at Thr308 (1 h: -29%, 3 h: -38%; p < 0.05) and mTOR phosphorylation at Ser2448 (1 h: -10%; ns, 3 h: -21%; p < 0.05), both in the anabolic pathway. Phosphorylation of AMPK, ACC and ULK1 were not affected. c-MYC gene expression was unchanged following transcranial electrical stimulation, but rDNA transcription decreased (1 h: -28%, 3 h: -19%; p < 0.05). PGC1α-ex1b mRNA increased (1 h: 2.3-fold, 3 h: 2.6-fold; p < 0.05), which also correlated with vastus lateralis electromyography activity, while other PGC-1α variants were unchanged. Acute transcranial electrical stimulation of skeletal muscle in weight-bearing healthy individuals did not induce anabolic signalling, and some signs of impaired muscle anabolism were detected, suggesting limited potential in preventing muscle wasting.